2009
DOI: 10.1037/a0015128
|View full text |Cite
|
Sign up to set email alerts
|

Psychological trauma and physical health: A psychoneuroimmunology approach to etiology of negative health effects and possible interventions.

Abstract: People who have experienced traumatic events have higher rates than the general population of a wide range of serious and life-threatening illnesses including cardiovascular disease, diabetes, gastrointestinal disorders, and cancer. An important question, for both researchers and clinicians, is why this occurs. Researchers have discovered that traumatic events dysregulate the hypothalamic-pituitary-adrenal axis and sympathetic nervous system. More recently, research from the field of psychoneuroimmunology (PNI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
110
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 87 publications
5
110
0
5
Order By: Relevance
“…While previous research has suggested that reports of poor sleep in individuals with PTSD contribute to negative physical 62,63 and mental health outcomes, 21,61 our study demonstrates for the first time that sleep disturbance is also associated with reduced cognitive performance. The effect of sleep disturbance on neuropsychological test performance was wide-ranging, as it accounted for significant variance in all cognitive factors with the exception of manual dexterity.…”
Section: Discussionmentioning
confidence: 63%
“…While previous research has suggested that reports of poor sleep in individuals with PTSD contribute to negative physical 62,63 and mental health outcomes, 21,61 our study demonstrates for the first time that sleep disturbance is also associated with reduced cognitive performance. The effect of sleep disturbance on neuropsychological test performance was wide-ranging, as it accounted for significant variance in all cognitive factors with the exception of manual dexterity.…”
Section: Discussionmentioning
confidence: 63%
“…People who have experienced traumatic events have higher rates than the general population for cardiovascular disease, diabetes, cancer and gastrointestinal disorders (Kendall-Tackett, 2009). Specifically, trauma affects the functioning of the sympathetic nervous system and the endocrine system (Solomon & Heide, 2005).…”
Section: The Impact Of Trauma On Physiological Functioningmentioning
confidence: 99%
“…When the body is experiencing stress, it needs oxygen and glucose in order to fight or flee from the perceived danger. The brain then sends a message to the adrenal glands telling, them to release epinephrine (Kendall-Tackett, 2009). Epinephrine increases the amount of sugar in the blood stream, increases the heart rate and raises blood pressure.…”
Section: The Impact Of Trauma On Physiological Functioningmentioning
confidence: 99%
See 2 more Smart Citations